Gerakan Injili dan Panggilan Gereja Untuk Pertumbuhan Spiritualitas Jemaat - Gatsper A Lado; Enggar Objantoro; Joni Aihery (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Abstract: This paper specifically suggests how the evangelistic movement carried out by the church is related to the growth of congregational spirituality. The focus of this paper outlines how the evangelistic movement carried out by the church from the first, mid to the modern century. This article was written using qualitative methods with a literature study approach. The results of the presentation of this study suggest that the church is actively carrying out evangelistic movements aimed at the growth of congregational spirituality. This is captured when tracing churches in the first century, middle, modern, post-modern to the digital age. The evangelistic movement has always been a church identity aimed at the growth of congregational spirituality. In the evangelistic movement carried out by the church, there has always been a figure of missionary mobilization Luther and Calvin along with other figures. The evangelistic movement carried out by the church in response to the Great Commission so that the world undergoes a change in relation to knowing Jesus Christ through the growth of congregational spirituality.Keyword: Evangelistic Movement, Church, Spirituality, BelieversAbstrak: Tulisan ini secara spesifik mengemukakan bagaimana gerakan penginjilan yang dilakukan oleh gereja dalam kaitan pada pertumbuhan spiritualitas jemaat. Fokus dari tulisan ini menguraikan bagaimana pergerakan penginjilan yang dilakukan oleh gereja dari abad pertama, pertengahan, modern, dan sampai pada post modern. Artikel ini ditulis dengan menggunakan metode kualitatif dengan pendekatan studi kepustakaan. Hasil dari pemaparan kajian ini mengemukakan bahwa gereja secara aktif melakukan gerakan penginjilan yang bertujuan pada pertumbuhan spiritualitas jemaat. Ini terpotret bila menelusuri gereja pada abad pertama, pertengahan, modern, post modern sampai era digital. Gerakan penginjilan selalu menjadi identitas gereja yang bertujuan pada pertumbuhan spiritualitas jemaat. Di dalam gerakan penginjilan yang dilakukan oleh gereja, selalu ada tokoh penggeraknya misialnya Luther dan Calvin bersama tokoh lainnya. Gerakan penginjilan yang dilakukan oleh gereja sebagai respon pada Amanat Agung agar dunia mengalami perubahan dalam kaitan mengenal Yesus Kristus melalui pertumbuhan spiritualitas jemaat.Kata Kunci: Gerakan Penginjilan, Gereja, Spiritualitas, Orang Percaya